Naga’s Fireballs: A Mysterious Phenomenon on Mekong River and Local Buddhists’ Trust - คุณากโร (อัญโญ), พระมหาสมพงษ์ (วารสารพุทธอาเซียนศึกษา, 2023)
It is undeniable that the Buddhism talks about Naga (a sacred snake) as it appeared legendarily in early Buddhism. The legend of Naga has strong effects to Buddhist Thai society, especially the Buddhists in Northeastern Thailand. The Buddhists therein believe in Naga in various roles such as protecting a life of people, bringing them some prosperity, etc. The Buddhists living their life along the basin of Mekong River strongly believe in the existence of living Naga as they have annually seen an appearance of the Naga, one of these is a fireball phenomenon on Mekong River; which is called the Naga’s fireball. Surprisingly, the appearance of mysterious phenomenon occurs on full moon day at 11th Thai lunar month which is annually falls on the day-end of Buddhist Lent. It is believed that the fireballs on Mekong River rise from the middle of the river up to sky and disappear without any clue. It results from the Naga who needs to cerebrate and commemorate the day when Buddha descended to the earth after living on the heaven for three months to give a sermon to his mother. To celebrate and commemorate, the Naga fires a fireball from his resident located beneath the Mekong River as the local Buddhists believed. The fireball phenomenon has considerably sparked Thais and tourists coming to visit the place where the fireballs rise from the river. More significant, many people from various sections of Thailand need to find out where the fireballs come from; whether from mysterious things, human beings, or natural causes.